2014
DOI: 10.1093/toxsci/kfu255
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Lung Injury and Inflammation in Mice: Role of Inducible Nitric Oxide Synthase and Surfactant Protein D

Abstract: Reactive nitrogen species (RNS) generated after exposure to radiation have been implicated in lung injury. Surfactant protein D (SP-D) is a pulmonary collectin that suppresses inducible nitric oxide synthase (iNOS)-mediated RNS production. Herein, we analyzed the role of iNOS and SP-D in radiation-induced lung injury. Exposure of wild-type (WT) mice to γ-radiation (8 Gy) caused acute lung injury and inflammation, as measured by increases in bronchoalveolar lavage (BAL) protein and cell content at 24 h. Radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Levels of iNOS have been correlated with increased inflammation in several infection models and can be a marker for the oxidative stress response [ 33 ]. There is also evidence for an association between increased vascular nitric oxide and severe dengue disease [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Levels of iNOS have been correlated with increased inflammation in several infection models and can be a marker for the oxidative stress response [ 33 ]. There is also evidence for an association between increased vascular nitric oxide and severe dengue disease [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a relationship between NOX2 and cell death has been detected for human liver cancer cell, lung cancer cells and cervical cancer cells [102]. The roles of other enzymes such as COX-2 and iNOS have been proposed for radiation induced chronic oxidative stress in the bone marrow, lung, heart and joints [103][104][105][106][107].…”
Section: Melatonin and Ros/no Producing Enzymes After Exposure To Radmentioning
confidence: 99%
“…Surfactant has also been shown to have a protective effect on the barrier function (134), and thus surfactant dysfunction may aggravate severity of lung edema and inflammatory cell infiltration. Furthermore, because a previous report showed that loss of SP-D may enhance sensitivity of the lung to hyperoxia-, ozone-, and bleomycininduced injury through inhibiting inducible nitric oxide synthase-mediated reactive nitrogen species production (169), it is reasonable that surfactant dysfunction may substantially increase susceptibility of lung cells to injurious stimuli. Interestingly, large genome-wide sequencing studies identified an association between mutations in SFTPC and SFTPA2, the gene encoding SP-C and -A2, and familial IPF (137), which accounted for up to 20% of IPF cases (137).…”
Section: Pathogenic Mechanisms Of Cell Wounding In Ards and Ipfmentioning
confidence: 99%